The Role of Architectural Awards for Enhancing Heritage-Based Graduation Projects Analytical Study of Tamayouz Excellence Award for Iraqi Students - Al-Qemaqchi, Naheth Taha (Sulaimani Journal for Engineering Sciences, 2020)
The cultural heritage plays an important role in determining the identity of any community, and the architectural output is at the forefront of this subject since it‟s the direct visual product of a cumulative result of the experience led by the communities within a given time and place which is compatible with the cultural structure and social life. From this point of view, the academic curriculum in many architectural schools tries to enhance the students‟ vision for the cultural heritage by introducing that heritage as a main source of inspiration in the creation of their design product. This comes in various ways, most of which are based on the employing of visual elements and external details showing their impact on the facades of the design projects as a blind repetition of that legacy, while some schools are investigating more deeply the ideology behind the production of that legacy and direct their students to study the deep structure of that heritage and reproduce it differently from previous to more contemporary architecture. The process of evaluating student‟s architectural products supports those approaches of inspiring heritage-based projects as those processes considered as an evaluating means for the outputs. One of the most important sources for those evaluations were students‟ project competitions and awards, which play a vital role in implicitly inspiring the cultural values of that heritage. Tamayouz Excellence Award for Graduation Projects stands on the head of these awards for the final stage output of Iraqi students. This paper aims to investigate the extent to which the academic output of the students' products which were chosen as a shortlist by (Tamayouz Excellence Award for Iraqi Students) can reflect the iconic, canonic, pragmatic, and analogy depiction of that heritage, and thus its ability to create a product with a deep local cultural vision. This is done by examining those output of several Iraqi architectural final stage students by analyzing those projects according to the structural elements that formulate their concepts, to point out those trends that help the promoting out values of identity within their works. The research found that the projects which inspire the heritage were not the most likely to run for the final positions. The reason for this lies in the superficial approach in which these projects dealt with the heritage values, and the local culture has been limited to the inspiration of the just formal elements without going deeply into the intellectual depth of that heritage.
Keywords: Identity; Heritage; Architectural pedagogy; Graduation projects; Tamayouz Excellence Award; Architectural concept tactics